In the multitude of words, sin is not lacking: an analysis of codes of ethics across Fortune 500 companies - Dall'Agnol, Matheus de Sena (2021)
Despite millions of dollars being deployed to few studies have been able to effectively address and measure the effectiveness of codes of ethics in reducing misbehavior. In this article, we propose to evaluate what information codes can highlight in terms of deeper ethical structures of organizations. We suggest that codes of ethics can be separated into two different contents: a legal approach, based on rational decision-making and mainly focused on the institutional legal framework, and a behavioral approach takes onboard insights from the behavioral ethics literature. To evaluate both the codes\' structure and development empirically, we decided to use Fortune 500\'s public companies dataset. Our results show that, via cluster analysis, three main code categories emerged: legalistic codes, behavioral codes, and paper codes – which have low proportions of both legal and behavioral content. Also, by evaluating the relationship between code effectiveness and content, we found that companies with higher behavioral content had a better compliance effectiveness system when measured as risk behavior. However, behavioral content fared worse when measured against the risk of class action litigations. We believe that our results may shed light on how to improve compliance policies better and how to build guidelines that effectively consider how key stakeholders effectively make ethical decisions. By structuring compliance guidelines that take into consideration the particularities of each organization, we will be one step closer to foster and create truly ethical organizations.